Determination of the industrial use of the limestones of the lagunitas formation, outcrops to the east of the municipality of Agustín Codazzi, Cesar-Colombia (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2022)
The Limestone rock has been of great utility and importance since ancient times, due to its physicochemical characteristics that allow its use for industrial purposes. In the municipality of Agustin Codazzi, limestones intercalated with shales outcrop, corresponding to the Lagunita Formation. The objective of this research is to know their geographic distribution, chemical composition and potential use as industrial material, by means of geochemical techniques (FRX), mapping, stratigraphic analysis, and Colombian Technical Norms 5163 and 4915. Texturally they correspond to wackestone, according to Dunham 1962, with presence of echinoderms, algae, fish bones, foraminifera and bivalves, which allow establishing a relative age between Barremian to Aptian; in general, they are constituted by SiO2 in 3.1%wt; P2O5 in 2.7%wt and CaO in 77 %wt. MgO in 0.7%wt, Al2O3 in 0.6%wt and Fe with 0.25%wt; and its main use is for the manufacture of cement and lime.
Keywords: Lime; Limestone; Cement; X-Ray Fluorescence; Geology; Petrography